The combustion and emission improvements for diesel–biodiesel hybrid engines based on response surface methodology - Li, Junming; Zhong, Weihuang; Zhang, Jian; Zhao, Ziheng; Hu, Jingyi (Frontiers in Energy Research, 2023)
With the rapid technological progress of society and increasingly stringent environmental regulations, further reduction of emissions has become an important issue for environmental protection. This study developed a response surface model with biodiesel blending ratio (BBR), load and EGR as independent variables and brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), NOx, HC and CO emission rates as dependent variables, and simulations were performed and calculated. The results show that according to the response surface approach with the objectives of maximizing BTE of the engine and minimizing BSFC, NOx emission and HC emission, it is concluded that when the BBR is 20%, the EGR rate is 15%, and the engine load is 74.52% can significantly reduce the pollutant emission while maximizing the engine power performance.